Physical and mechanical properties enhancement of lead free solders reinforced with carbon nanotubes: a critical review - Dele-Afolabi, T. T.; Mohamed Ariff, Azmah Hanim; Mazlan, Norkhairunnisa; Mohamed Yusoff, Hamdan (American-Eurasian Network for Scientific Information, 2014)
Owing to the great advancement in technology, the input/output terminals in electronic packaging have greatly increased resulting to a proportional increase in solder interconnection joints of electrical components. Therefore, in order to work in line with the mission and vision of the electronic industries which are the production of more powerful, efficient and miniaturized gadgets, it is imminent to introduce alloying elements to the existing lead free conventional solders which will possibly lead to the enhancement of electrical and mechanical properties of the interconnection joints. An attempt has been made to reveal an element of desirable properties which can meet the demands of the micro systems and electronics industries. A documentation of the benefits that the carbon nanotubes CNTs can yield has been presented in previous studies which therefore serve as the primary reason for embarking on this review report.